2017
DOI: 10.1039/c7ra04563h
|View full text |Cite
|
Sign up to set email alerts
|

Hydrotropic polymer-based paclitaxel-loaded self-assembled nanoparticles: preparation and biological evaluation

Abstract: Hydrotropic polymer-based paclitaxel-loaded self-assembled nanoparticles: preparation and biological evaluation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 30 publications
1
8
0
Order By: Relevance
“…This hydrophobic part interacts with the drug molecules, and the ionic part increases the water solubility. The solubilization method is very nuanced, and the decision can be summed up in four ways: hydrophobic interaction, accumulation of aromatic rings, formation of a hydrogen bond, and unique point-to-point interaction. , Paul et al reported the enhanced solubility of griseofulvin in water using hydrotrope sodium cumene sulfonate (SCS) and its delivery to the γ-tubulin protein. In the presence of SCS molecules, it has been found that the drug–protein interaction is not very strongly affected.…”
Section: Applicationmentioning
confidence: 99%
“…This hydrophobic part interacts with the drug molecules, and the ionic part increases the water solubility. The solubilization method is very nuanced, and the decision can be summed up in four ways: hydrophobic interaction, accumulation of aromatic rings, formation of a hydrogen bond, and unique point-to-point interaction. , Paul et al reported the enhanced solubility of griseofulvin in water using hydrotrope sodium cumene sulfonate (SCS) and its delivery to the γ-tubulin protein. In the presence of SCS molecules, it has been found that the drug–protein interaction is not very strongly affected.…”
Section: Applicationmentioning
confidence: 99%
“…The particle size determined by DLS represented the hydrodynamic diameter, whereas the results obtained by TEM were the collapsed nanoparticles aer water evaporation. 32 Moreover, the drug loading (DL) was measured to further evaluate the nanoparticles. The DL of PGA-PTX, PGA-GEM and PGA-FA were 18.6%, 19.56% and 19.4% respectively, and the experimental results were as expected as theory.…”
Section: Preparation and Characterization Of Functionalized Nanoparticlesmentioning
confidence: 99%
“…In addition, it has shown a series of advantages such as high water solubility and drug-loading capacity, good biocompatibility, low toxicities, improved tumor-targeting ability, and antitumor efficacy. 13,14 To increase the tumor-targeting ability of PDCs, the most common way is to conjugate a targeting moiety to the polymer backbone by covalently chemical modification 8,15,16 to prepare a so-called actively targeting PDCs. For example, conjugation of iRGD to N-(2-hydroxypropyl)methacrylamide (HPMA) copolymer 17,18 or doxorubicin−polymer conjugates 19 resulted in an enhanced tumor accumulation and penetration.…”
Section: ■ Introductionmentioning
confidence: 99%
“…This is also in accordance with many previous reports. 13,14 According to the drug-loading equation, the PTX loaded in PGG−PTX, mPEG/PGG−PTX, and RGE−PEG/PGG−PTX NPs were 35.1%, 32.5%, and 31.6%, respectively, indicating that the modification of RGE peptide through physical encapsulation did not affect the loading capacity of the PGG−PTX delivery system. In addition, our drug-delivery system showed a good stability in vitro over 3 weeks (Figure 4).…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation